The Influence of Using Chatbot Towards Junior High School Students’ Vocabulary Mastery - Ramdhani, Muhamad; Juniardi, Yudi; Miranty, Delsa (Journal of English Language Teaching and Cultural Studies, 2024)
This research aimed to determine the influence of using chatbot on students’ vocabulary mastery in class VII SMPN 13 Cirebon. This research used quantitative research method by implementing quasi-experimental research design. The participants in this study were 48 students from two classes. VII E served as experimental class and VII D control class. This research used purposive cluster sampling as the sampling technique. This research used a test as an instrument and is analyzed by using IBM SPSS 25. The research finding showed that the post-test mean score in experimental class was higher than control class (70,00 > 68,96). This result means students’ vocabulary mastery improving in experiment class was better than control class. Furthermore, the t-test result showed that sig (2-tailed) was less than 0,05 (0,029 < 0,050). This result meant null hypothesis (H0) was rejected and alternative hypothesis (Ha) was accepted. In addition, there is low effect in using Chatbot towards junior high school students’ vocabulary mastery. Therefore, this indicated that there was an influence of using chatbot on seventh-grade students’ vocabulary mastery at SMPN 13 Cirebon.